Сlinical anatomy - the basis of modern morphology and surgery. - Vovk, Y. N. (Морфологія / Morphologia / Morfologìâ, 2016)
The clinical importance and place of topographic anatomy and operative surgery in the system of higher medical education in our country are still remain complex and controversial. Everywhere there is a separate discipline "Clinical anatomy", which is taught in all developed and modern universities in the USA, Europe, Asia and Africa. According to the new curriculum approved in 2015 topographical anatomy with clinical operative surgery is related to the "Surgery", which consists of 10 training modules. The first two modules are our discipline, which is intended for the acquisition of clinical knowledge in anatomy on the 2nd and 3rd course (4th-5th semesters). I would not like to dwell on the "deplorable" volume of the curriculum and hours dedicated to lectures and practical classes. What can we teach students in the third year, if the lessons of topographical anatomy and operative surgery are held once in two weeks - a total of 20 hours of training (10 workshops). In this regard, I once again call on the medical community, the Ministry of Health and Ministry of Education of Ukraine, and all who are not indifferent to doctors asking the right attitude and understanding of the current value and the location of the clinical anatomy and operative surgery in our system of higher medical education. I'm staying at the position of a primary role of our discipline in training of medical specialists on the modern world level, following the best traditions and achievements of our surgery created by NI Pirogov.